Is There a Real Relationship between the Presence of Helicobacter pylori in Dental Plaque and Gastric Infection? A Genotyping and Restriction Fragment Length Polymorphism Study on Patient Specimens with Dyspepsia in Southwest Iran - Moosavian, Mojtaba; Kushki, Elyas; Navidifar, Tahereh; Hajiani, Eskandar; Mandegari, Mahdi (International Journal of Microbiology, 2023)
Background. The oral cavity can act as an extra gastric reservoir for H. pylori, and the presence of the bacteria in the oral cavity is associated with a higher risk of dental caries development. This study aimed to determine the genotype and evaluate the association between the presence of H. pylori in dental plaque and gastric biopsy specimens in dyspeptic patients in Ahvaz, Southwest Iran. Methods. In this study, 106 patients with recruited dyspeptic complaints were selected, and from each patient, two gastric antral biopsy specimens and two dental plagues were examined. The presence of H. pylori was identified by the rapid urease test (RUT) and the amplification of ureAB and 16S rRNA genes. Also, to verify a hypothetical mouth-to-stomach infection route, the enzymatic digestions of three genes of cagA, vacA, and ureAB in H. pylori strains isolated from dental plaques and stomach samples were compared for each same case. Results. H. pylori was found in the stomach of 52.8% (56/106) and the dental plaques of 17.9% (19/106) of the studied cases. On the other hand, H. pylori was recognized in the stomach of all 19 cases with oral colonization. Following a combination of restriction fragment lengths 21 polymorphism (RFLP) patterns of these three known genes on stomach and dental plague samples, 14 and 11 unique patterns were seen, respectively. However, for all H. pylori-positive cases (19), the comparison of RLFP patterns of these genes in dental plaque and gastric biopsy specimens was different for the same case. Conclusions. In this study, it seems that there is no significant association between the presence of H. pylori in dental plaque and the stomach of the same case.